2017
DOI: 10.3389/fmed.2017.00144
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Premenstrual Symptoms Predicted by Second to Fourth Digit Ratio

Abstract: Women of reproductive age often experience a variety of unpleasant symptoms prior to the onset of menstruation. While genetics may influence the variability of these symptoms and their severity among women, the exact causes remain unknown. We hypothesized that symptom variability originates from differences in the embryonic environment and thus development caused by variation in exposure to sex hormones. We measured the second to fourth digit ratios (2D:4D) in 402 young women and investigated the potential rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…The effects of the menstrual cycle on the brain network properties might be different between the low and high digit ratio groups, because a permutation test more often revealed differences in brain regions (five regions) in the low digit ratio groups than in the high digit ratio group (three regions) for the global hubs and global nodes in a different manner (Figure ). The results may be related to the previous our study that showed women with a higher right 2D:4D ratio had lower premenstrual symptom severity (Kaneoke et al., ). Similar results were observed for the data with preprocessing 2 (Figure S9).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The effects of the menstrual cycle on the brain network properties might be different between the low and high digit ratio groups, because a permutation test more often revealed differences in brain regions (five regions) in the low digit ratio groups than in the high digit ratio group (three regions) for the global hubs and global nodes in a different manner (Figure ). The results may be related to the previous our study that showed women with a higher right 2D:4D ratio had lower premenstrual symptom severity (Kaneoke et al., ). Similar results were observed for the data with preprocessing 2 (Figure S9).…”
Section: Discussionsupporting
confidence: 75%
“…Third, according to our recent study, females with a lower digit ratio of the right hand tend to have greater premenstrual symptoms (Kaneoke et al., ). Thus, our low digit ratio group may have more participants with premenstrual syndrome and premenstrual dysphoric disorder than the high digit ratio group, which could affect the results (Comasco & Sundstrom‐Poromaa, ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…McIntyre et al and Richards et al found a significant positive association between right 2D:4D and estradiol levels across menstrual cycle 28,29 , although Klimek et al found no such correlation 43 . In addition, Kaneoke et al found a negative association between right 2D:4D and severity of premenstrual symptoms 27 . These findings along with our finding regarding age at menarche support the association between 2D:4D and menses characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…menarche [20][21][22][23] , puberty characteristics 24 , reproductive period 20 , age at menopause 25 , polycystic ovary syndrome 26 , severity of premenstrual symptoms 27 and estradiol levels across menstrual cycle 28,29 . Several studies found 2D:4D to be associated with reproductive cancers 25,30,31 .…”
mentioning
confidence: 99%